The Influence of Study Discipline, Study Motivation, and Peer Environment on Student Learning Outcomes in Islamic Religious Education - Achmad Nur Rofiuddin; Amir Bandar Abdul Majid; M. Yusron Maulana El-Yunusi (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Learning outcomes are one of the important indicators of the success of the educational process, which are influenced by various internal and external factors. In reality, students’ learning outcomes in Islamic Religious Education are still varied, indicating the need to examine factors such as study discipline, learning motivation, and peer environment. This study aims to analyze the influence of study discipline, learning motivation, and peer environment on students’ learning outcomes in Islamic Religious Education at Darul Ulum Waru Junior High School, Sidoarjo. This research employed a quantitative approach using a survey method. The population consisted of 255 students, with a sample of 162 students selected through convenience sampling. Data were collected using questionnaires and analyzed using multiple linear regression analysis. The results of the study indicate that learning motivation has a positive and significant effect on students’ learning outcomes, while study discipline does not have a significant effect. In addition, the peer environment also has a positive and significant influence on learning outcomes. These findings suggest that improving students’ learning motivation and fostering a positive peer environment play a crucial role in enhancing learning outcomes in Islamic Religious Education.